2019
DOI: 10.31083/j.jin.2019.04.188
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory rhythm generation and pattern formation: oscillators and network mechanisms

Abstract: J o u r n a l o f I n t e g r a t i v e N e u r o s c i e n c e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 516 publications
(587 reference statements)
0
18
0
Order By: Relevance
“…How the neuronal network in the posterior MG and ACINs autonomously expresses alternating tail beats with a ~20-s cycle period is an interesting question. In mammalian brain-slice preparations, "autonomous" rhythm-generating neural circuits have been found, including motor pattern/rhythm centers for breathing such as medullary preBötzinger and Bötzinger complexes (Smith et al, 1991;Koshiya and Smith, 1999;Ghali, 2019).…”
Section: The Mid-piece Of the Ciona Larva Expresses An Autonomous Cycle Period Of Tail Beating Burstsmentioning
confidence: 99%
“…How the neuronal network in the posterior MG and ACINs autonomously expresses alternating tail beats with a ~20-s cycle period is an interesting question. In mammalian brain-slice preparations, "autonomous" rhythm-generating neural circuits have been found, including motor pattern/rhythm centers for breathing such as medullary preBötzinger and Bötzinger complexes (Smith et al, 1991;Koshiya and Smith, 1999;Ghali, 2019).…”
Section: The Mid-piece Of the Ciona Larva Expresses An Autonomous Cycle Period Of Tail Beating Burstsmentioning
confidence: 99%
“…In the current study all ocular and brain cell types and tissues exhibited easily detectable ACE2 receptor signals, and in agreement with previous reports underscore the ubiquitous nature of ACE2 receptor expression throughout the human visual system and CNS (Figures 1 and 2) [5,6,24].Importantly, and as indicatedin previous studies,negative controls, yeast and microbial RNA controls,synthetic homoribonucleotide polymers and random oligonucleotides showed no expression of the ACE2 receptormRNA [6]. The highest expression of ACE2 mRNA in the brain was found in the brainstem region known as the pons, situated anterior to the cerebellum between the midbrain and medulla oblongata, and an important relay center known to conduct signals from the cerebrum,through to the cerebellum and medulla oblongata,including ber tracts that involve the transmission ofvisual sensory signals into the thalamus [36,37].The pons is known to contain neural circuits that deal primarily with the regulation of respiration, taste (aguesia), audition, saccadic eye movement, facial sensation and expression and equilibrium,all of which are known to be affected or disrupted in COVID-19 disease [7,17,24,25,[36][37][38]. The respiratory tract connects to the brain without the protection of a blood-brain barrier, and that SARS-CoV-2 might in the early invasive phase attack the cardiorespiratory regulatory nodes located in the pons and medulla oblongata, giving rise to both respiratory and cardiac disruption is also commonly observed in COVID-19 patients [25,[38][39].The highest expression of the ACE2 receptor protein in the ocular cells and brain tissues involved in visual signaling and examined in this study were found in ocular choroid broblasts andretinal pigment epithelial (RPE) cells, a monolayer of pigmented cells of neuro-ectodermal origin situated between the neurosensory retina and the choroid that nourishes the visual photoreceptor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, and as indicated in previous studies, negative controls, yeast and microbial RNA controls, synthetic homo-ribonucleotide polymers and random oligonucleotides showed no expression of the ACE2 receptor mRNA [ 6 ]. The highest expression of ACE2 mRNA in the brain was found in the brainstem region known as the pons, situated anterior to the cerebellum between the midbrain and medulla oblongata, and an important relay center known to conduct signals from the cerebrum, through to the cerebellum and medulla oblongata, including fiber tracts that involve the transmission of visual sensory signals into the thalamus [ 36 , 37 ]. The pons is known to contain neural circuits that deal primarily with the regulation of respiration, taste (aguesia), audition, saccadic eye movement, facial sensation and expression and equilibrium, all of which are known to be affected or disrupted in COVID-19 disease [ 7 , 17 , 24 , 25 , 36 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Preinspiration comes from a nucleus of the brain stem, the pre-Bötzinger complex (preBötC). This contains about 20% of autonomous depolarization activity (pacemaker) and is probably due to a balanced interchange of cationic currents between calcium and sodium [20, 21]. The preBötC neurons implement a ramp-like depolarization, for a maximum of 100–400 ms (preinspiratory phase), before carrying out the impulse of the active inspiration, or the second phase of the eupneic cycle [22].…”
Section: The Respiratory Neural Networkmentioning
confidence: 99%
“…The inspiratory phase begins when the preBötC reaches a complete depolarization of its neurons, about 13% of which are able to synchronize the neurons of the contralateral preBötC [19]. The ramp-like depolarization and complete depolarization of the preBötC are modulated by various central information areas (cerebellum, midbrain, cortical and subcortical centers), as well as by peripheral afferents monitoring quantity of blood oxygen, along with mechanical changes in the lungs and large vessels [21]. In the inspiratory phase, the preBötC continues with the stimulation of the cranial nerve XII, starting to stimulate the premotor neurons and the medullary phrenic motor neurons (from C 1 to C 5 ).…”
Section: The Respiratory Neural Networkmentioning
confidence: 99%